2020
DOI: 10.1111/obr.13151
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and thematic synthesis of qualitative studies exploring GPs' and nurses' perspectives on discussing weight with patients with overweight and obesity in primary care

Abstract: Summary Guidelines and evidence suggest primary care clinicians should give opportunistic interventions to motivate weight loss, but these rarely occur in practice. We sought to examine why by systematically reviewing qualitative research examining general practitioners' (‘GPs’) and nurses' views of discussing weight with patients. We systematically searched English language publications (1945‐2018) to identify qualitative interview and focus group studies. Thematic methods were used to synthesise the findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 57 publications
1
54
0
Order By: Relevance
“…Previous research suggests physicians are concerned about offending their patients if they discuss weight management 7 , 26 and do not see it as priority. 10 However, this study suggests discussions may be welcomed if the focus is on health, and patients are able to decline such conversations. Moreover, many jurors felt it would be the doctor's duty to have those conversations.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous research suggests physicians are concerned about offending their patients if they discuss weight management 7 , 26 and do not see it as priority. 10 However, this study suggests discussions may be welcomed if the focus is on health, and patients are able to decline such conversations. Moreover, many jurors felt it would be the doctor's duty to have those conversations.…”
Section: Discussionmentioning
confidence: 84%
“… 7 , 8 , 9 A recent systematic review and thematic synthesis of 29 qualitative studies exploring GPs' and nurses' perspectives on discussing weight with patients with overweight and obesity in primary care highlighted that discussing weight is not perceived to be a priority for GPs. 10 …”
Section: Introductionmentioning
confidence: 99%
“…However, none of these studies has focussed on weight‐related long‐term conditions. A recent review of qualitative studies with primary care staff 14 found mixed views about whether there was enough evidence to support GPs to advise people who are overweight (there is). Even among those who did see it as “part of the job” to advise weight‐management, some suggested that limited time in the consultation meant that staff prioritized other, more effective, discussions 14 …”
Section: Discussionmentioning
confidence: 99%
“…Health professionals report embarrassment and concern about offending patients who are overweight, and some are unconvinced that people who are overweight will successfully make changes 8,11,13 . A recent review concluded that discussions about weight management are not a high priority for GPs 14 . However, surely GPs should not feel reluctant to raise the topic when the patient has a known, weight‐related long‐term health condition?…”
Section: Introductionmentioning
confidence: 99%
“…Concern about regain in weight and the long term value of attempts at weight loss has been identified as a barrier to engagement in behavioural weight loss programmes from patients and healthcare providers. 2 Considerable research has been done on developing and testing specific weight loss maintenance programmes, but with little success. 3 4 Programmes have achieved modest success, with behavioural support intended to promote lasting adherence to changes in diet and increased physical activity.…”
Section: Introductionmentioning
confidence: 99%